5G network stereo coverage scheme in subway scenario - Xi WANG; Zheng YANG; Peng ZHANG; Qin SHU; Xin PAN (物联网学报)
As an urban artery and popular means of transportation, the subway is the most sustainable way of transportation.With the increase in operating mileage and passenger volume of subway and other rail transit, it faces greater challenges in operation, maintenance, security, scheduling, and other aspects.There is an urgent need for information technology to improve the level of subway operation services.While the foundation of subway informatization is effective indoor network coverage.At present, there are coverage requirements of multiple scenario such as outdoor wide area, indoor enclosed static scenes, and indoor enclosed high-speed sports scenes.For different coverage scenarios, if the same network method is chosen for coverage, there may be problems of high cost and poor coverage effect.Therefore, for the coverage of the subway network, it is necessary to flexibly combine macro station, micro station, room separation, leakage cable and other methods, combined with resource block (RB) guarantee, automatic handover, automatic login and other guarantee technologies, to meet the requirements of the network’s indicators such as insensitive switching, high data rate, low latency, high capacity, and large-scale connection under the optimal cost conditions, to ensure the normal operation of toB and toC business in subway scenarios.The 5G network stereo coverage scheme was studied in subway scenario, providing important reference for the coverage of other subway specialized networks.